(untitled) (Revista de Estudos da Linguagem, 2024)
The following paper provides an analysis of soccer terms and specialized phraseological units in metaphorization processes with the target area of politics. The research uses a monolingual journalistic corpus in Spanish rio-platense, from the politics section Humor Político of the Argentinean newspaper Clarín. The use of computer programs for lexical analysis typical of Corpus Linguistics research has made it possible to identify and extract terms and specialized phrases found in the corpus. The analysis of units in context pointed to the metaphorical construction of the most abstract field of politics by means of more concrete figures of the soccer environment. The corpora consultation available online corroborated the premises and findings in the corpus of study.